Membangun Sistem Manajemen Mutu Untuk Usaha Kecil Menengah : (Sebuah Upaya Menjamin Mutu Produk UKM) - Filta Filta; Monika Handojono; Harry Anthony P Sitaniapessy (Jurnal Administrasi Terapan, 2023)
UD Filkin Mebel produces and sells a variety of furniture products using an order system. With the traditional techniques and processes used, it turns out that the product failure rate is quite a lot. This research aims to build a simple Quality Management System that can be applied to small and medium enterprises (SMEs) based on ISO 9001: 2015 to reduce failures and improve product quality. By using descriptive qualitative research methods, the author analyzes the data by describing the data that has been collected as it is. The research produces a simple quality management system that can be applied in improving quality at UD. Filkin Furniture.